2021
DOI: 10.1111/1744-9987.13732
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac geometry, function, and remodeling patterns in patients under maintenance hemodialysis and peritoneal dialysis treatment

Abstract: Cardiovascular disease is the leading cause of mortality in patients with end‐stage‐kidney disease. Evidence on the possible echocardiographic differences between hemodialysis and peritoneal dialysis (PD) is scarce. This study aimed to evaluate differences in left (LA) and right atrial (RA), left (LV) and right ventricular (RV) geometry, systolic and diastolic function in hemodialysis, and PD patients. Thirty‐eight hemodialysis and 38 PD patients were matched for age, sex, and dialysis vintage. Two‐dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…36 Moreover, other studies showed similar levels of office and ambulatory pulse wave velocity between the two dialysis modalities, 37,38 suggesting no differences in arterial stiffness. Finally, as cardiac hypertrophy is considered to impact the cardiopulmonary reflex and chemosensitive receptors control, the largely similar cardiac geometry, systolic and diastolic function indices between HD and PD, 35 could also explain -at least in partour findings. As such, our findings are in general agreement with previous works that have evaluated other parameters related to sympathetic versus parasympathetic balance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…36 Moreover, other studies showed similar levels of office and ambulatory pulse wave velocity between the two dialysis modalities, 37,38 suggesting no differences in arterial stiffness. Finally, as cardiac hypertrophy is considered to impact the cardiopulmonary reflex and chemosensitive receptors control, the largely similar cardiac geometry, systolic and diastolic function indices between HD and PD, 35 could also explain -at least in partour findings. As such, our findings are in general agreement with previous works that have evaluated other parameters related to sympathetic versus parasympathetic balance.…”
Section: Discussionmentioning
confidence: 97%
“…Factors like total small solute clearance, volume overload, blood pressure (BP) control, subclinical inflammation, anemia prevalence, and others were commonly found to be no different between HD and PD patients. 19,3235 Elegant studies examining vascular function also suggest that these parameters were similar between HD and PD. In a recent study of our group, including 38 HD patients, 38 PD patients, and 38 controls, endothelial postocclusive forearm skin vasodilatory response assessed with laser speckle contrast imaging (an index of endothelial dysfunction) did not differ between HD and PD patients but was significantly impaired in both ESKD groups compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients who receive dialysis develop anemia. Some scholars have reported that left ventricular mass index and Hb are negatively correlated in peritoneal dialysis patients [ 21 ]. In anemia, the number of red blood cells decreases, which can trigger a decrease in blood viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…A continuous decrease in the E/E′ ratio was observed in patients undergoing dialysis. Nevertheless, a previous study showed no significant difference in E/E′ between patients on HD versus PD 24 . A study of patients with PD followed them for 3 years to determine the dynamic changes in LV structure and function.…”
Section: Discussionmentioning
confidence: 78%